Effect of Temperature and Drying Time on Chemical Characteristics and Sensory of Tabah Bamboo Leaf Tea (Gigantochloa nigrociliata BUSE-KURZ)v - Wirawan, I Kadek; Kencana, Pande Ketut Diah; Utama, I Made Supartha (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
This study aimd to determine the effect of temperature and drying time on the chemical and sensory characteristics of Tabah bamboo leaf tea. This study was designed using a Completely Randomized Design (CRD) with two factors, namely the drying temperature factor (50oC and60oC) and the drying time factor (1 hour, 2 hours, and 3 hours). The treatment was repeated three times to obtain 18 experimental units. The parameters observed were water content, pH, total acid, total phenol, color, aroma, taste, and overall acceptance tested organoleptically. The results showed that the interaction of temperature and duration of drying of Tabah bamboo tea leaves had a significantly different effect on water content, pH, total acid, total phenol, color, overall reception, but did not have a significantly different effect on aroma and taste. The best treatment was water content 6.881%, pH 6.6, total acid 0.73%, total phenol 84.01 mg/100g, color 4.33, aroma 4.47, taste 4.27 and overall acceptance 4.47.